Preclinical evidence and possible mechanisms of β-asarone for rats and mice with Alzheimer's disease: A systematic review and meta-analysis - Xin-Yuan Du; Xin-Yuan Du; Yu-Shuang Cao; Yu-Shuang Cao; Juan Yang; Juan Yang; Li-Chen Guo; Li-Chen Guo; Tong Zhang; Tong Zhang; Qing Yuan; Qing Yuan; et al. (Frontiers Media S.A., 2022)
Background: Currently, there are many different drugs to improve Alzheimer's disease (AD) from different pathways. As a supplement and alternative medicine, traditional Chinese medicine (TCM) targets multiple pathways which may be different from classical Western medicine, which may be orchestrated with Western medicine to materialize multiplying efficacy in AD patients.Objective: To investigate the therapeutic effect and assess the available preclinical evidence and possible mechanisms of β-asarone which was extracted from Acorus gramineus Soland (Araceae, AGS) for AD based on rat and mouse animal models.Methods: PubMed, Embase, Scopus, Cochrane Library, BIOSIS Previews, Web of Science, EBSCO, and Google Scholar were searched from inception to 5 May 2022. Rat and mouse experiments assessing the therapeutic effects of β-asarone for AD were included. Primary outcomes were neuroethology, including escape latency and times of crossing platform. Second outcomes were cell apoptosis, including Bax and Bcl-2. The weighted mean difference (WMD) was generated for continuous variables. The relative outcomes were analyzed with the aid of Get Data Graph Digitizer 2.26 and software STATA version 16.0 MP.Results: For the primary endpoint, compared with the modeling group, β-asarone significantly decreased the escape latency (WMD = -12.61, 95% CI: -18.66 to -6.57) and increased the times of crossing platform (WMD = 1.50, 95% CI: 0.31-2.70). For the secondary endpoint, β-asarone remarkably reduced the relative expression of the amyloid precursor protein (APP) (WMD = −2.25, 95% CI: −2.49 to −2.01), decreased the expression of the apoptosis-related protein, associated X protein (Bax) (WMD = −2.40, 95% CI: −3.51 to −1.29), lowered the expression of apoptosis-related protein, B-cell lymphoma-2 (Bcl-2) (WMD = 0.42, 95% CI: 0.38-0.46), and decreased the signal pathway-related proteins, phosphatidylinositol-3-kinase/protein kinase B (PI3K/AKT) (WMD = −0.70, 95% CI: −0.93 to −0.47) over the control group.Conclusion: β-asarone spectacularly improved the learning ability and memory in rats and mice, which might be correlated with its potential neuroprotective effect through multiple signaling pathways.